Monitoring of State in Program Simulator of Electronic Device - Czeberkus, Piotr; Timofeev, Alexander (Studia Informatica. System and information technology, 2007)
The article presents the interactive method of state monitoring of electronic device in autonomous simulated application. Form of electronic device state presentation is discussed. The information about state is presented by means of a special template, which can include both text and graphics. Author of model can decide about the format of displayed results. Implementation of the subsystem for monitoring electronic devices states, simulation course and observation of results are described. It is coming in sight, that the interactive monitoring of simulated devices state by means of text and graphics is readable, intelligible and more user friendly, and also it helps to understand better the processes, which take place in simulated devices and it is a good solution for didactics reasons.